Are CEOs Different? - KAPLAN, STEVEN N.; SORENSEN, MORTEN (Journal of Finance, 2021)
ABSTRACT Using 2,603 executive assessments, we study how CEO candidates differ from candidates for other top management positions, particularly CFOs. More than half of the variation in the 30 assessed characteristics is explained by four factors that we interpret as general ability, execution (vs. interpersonal), charisma (vs. analytical), and strategic (vs. managerial). CEO candidates have more extreme factor scores that differ significantly from those of CFO candidates. Conditional on being considered, candidates with greater general ability and interpersonal skills are more likely to be hired. These and our previous results on CEO success suggest that boards overweight interpersonal skills in hiring CEOs.